The Processing of Tuna Fish (Thunnus sp) in Ternate City - Darmawaty, Darmawaty; Djamhur, Martini; Achmad, M. Djanib; Muksin, Darmiyati (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
One of the leading commodities of Ternate is Tuna fish. Tuna dominates with a percentage of 23.17% or 10,326 tons of the total catch landed in Ternate in 2019 (Ibrahim and Renjaan 2021). Tuna is a large pelagic fish that has a high protein content, which is between 22.6-26.2 g/100 g of meat and contains a low-fat content of 0.2-2.7 g/100 g of meat. The magnitude of the potential of tuna fish resources in Ternate must be utilized properly in order to be able to move the community's economy through the development of the potential of superior fish resources. Tuna is a fish which is favored by the community because it has a delicious taste and high nutritional value. However, the use of tuna in Ternate so far has only been processed into smoked fish (commonly called tuna fufu), grilled, shredded, fried, or cooked in rica-rica. One way that can be done is by diversifying processed tuna fish, namely by processing it into Rendang which can be used as icons and signature souvenirs of Ternate City. The problem faced by the residents of Tobololo Village is the lack of knowledge about how to process fish into fish rendang, so it is necessary to conduct training in making tuna fish rendang. The training methods provided are counseling and product demonstrations. After completing the training, the participants had the knowledge and skills to make tuna fish rendang.